The emergence of boundary clusters in inter-organizational innovation. Issue 1 (January 2015) - Rehm, Sven-Volker; Goel, Lakshmi
Abstract Firms that want to innovate often do so by conducting cooperative innovation activities with business partners. In such inter-organizational cooperations, business partners depend on each other's knowledge and bring in different types of expertise. In our research we focus on the knowledge exchanges across knowledge boundaries in inter-organizational activities for innovation. Information systems (IS) play an important role as enablers in this context. The concept of boundary objects has been used to describe interactions between actors with varying information and knowledge needs. While the vital role of boundary objects has been recognized in IS literature, the process of emergence of boundary-spanning has received less attention. Recent literature has hinted that, contrary to initial conceptualizations, boundary objects may not manifest as only single information technology artifacts. In this study, we offer the view of boundary objects as a cluster of several artifacts. By means of a qualitative case study, we describe the process of emergence of such boundary clusters and provide evidence for how they advance inter-organizational innovation activities. We describe how such clusters emerge from differences and dependencies in the knowledge of cooperating actors and explore the clusters' significance to knowledge exchanges in inter-organizational innovation contexts. In doing so, we offer an explanation of cluster emergence which links the interplay of artifacts, uses, practices, and knowledge to the coordination of cooperative inter-organizational innovation activities.